Effect of breastfeeding on metabolic-related outcomes in women with previous gestational diabetes mellitus: A protocol for systematic review and meta-analysis. Issue 8 (26th February 2021) - Zhou, Bingfeng; Zhou, Jun
Abstract: Background: This meta-analysis was to systematically investigate the effect of breastfeeding on metabolic-related outcomes in women with previous gestational diabetes mellitus (GDM). Methods: We will search the online databases of Relevant studies were searched in Pubmed, Embase, Cochrane Library, Web of Science. Relative risk and weighted mean difference with 95% confidence interval will pooled using Stata14.0 software. Conclusion: Our meta-analysis will explore the effect of breastfeeding on metabolic-related outcomes in women with previous GDM and may provide effective treatment options of GDM. OSF registration number: 10.17605/OSF.IO/HA5U8